Using the Consolidated Framework for Implementation Research to design and implement a perinatal education program in a large maternity hospital - Sheridan Guyatt; Megan Ferguson; Michael Beckmann; Shelley A. Wilkinson (BMC, 2021)
Abstract Background Implementation science aims to embed evidence-based practice as 'usual care' using theoretical underpinnings to guide these processes. Conceptualising the complementary purpose and application of theoretical approaches through all stages of an implementation project is not well understood and is not routinely reported in implementation research, despite call for this. This paper presents the synthesis and a collective approach to application of a co-design model, a model for understanding need, theories of behaviour change with frameworks and tools to guide implementation and evaluation brought together with the Consolidated Framework for Implementation Research (CFIR). Method Using a determinant framework such as the CFIR provides a lens for understanding, influencing, and explaining the complex and multidimensional variables at play within a health service that contribute to planning for and delivering effective patient care. Complementary theories, models, frameworks, and tools support the research process by providing a theoretical and practical structure to understanding the local context and guiding successful local implementation. Results This paper provides a rationale for conceptualising the multidimensional approach for implementation using the worked example of a pregnancy, birth, postnatal and early parenting education intervention for expectant and new parents at a large maternity hospital. Conclusion This multidimensional theoretical approach provides useful, practical guidance to health service researchers and clinicians to develop project specific rationale for their theoretical approach to implementation projects.